Evaluation of awareness and knowledge of antibiotic use of patients applying to a community pharmacy - RABUŞ, ŞULE (My University, 2022)
Background and Objective: Infectious diseases constitute a large share of the diseases in the world. The use of irrational antimicrobial treatments causes failure in the treatment and toxic side effects in the patient.The aim of our study is to evaluate the knowledge level and attitudes of the patients who applied to the community pharmacy with an antibiotic prescription regarding the use of antibiotics. Setting and Method: This cross-sectional study was conducted in one community pharmacy in Istanbul (Turkey) between November 2021- February 2022. Each patient’s profile was recorded and a selfstructured questionnaire consisted 14 questions was administered to the patients who applied to the pharmacy with an antibiotic prescription. The questionnaire, which was prepared by the researchers on the basis of the relevant literature studies (1,2) and the answer options were determined as ‘‘true, false, I do not know’’. The questionnaire results were scored according to the relevant articles. All data were analyzed using the Statistical Package for the Social Sciences (SPSS Inc., Chicago, IL, USA) version 13. Main outcome measures: To evaluate the knowledge level and attitudes of the patients regarding the use of antibiotics. Results: Of the 39 patients 66.7% were female, and the mean age was 35.2 ± 1.6. Sixty-one percent of the patients were not working in any job. The majority of the patients (79.5%) applied to the pharmacy with the diagnosis of upper respiratory tract disease. The mean awareness score of the patients regarding the use of antibiotics was determined as 7.8 ± 0.4, and it was found to be higher in those who were actively employed than in those who did not (8.8 ± 0.5 vs. 7.1 ± 0.4; p = 0.022). It was determined that 77% of the patients had a moderate level of knowledge about antibiotics. Conclusion: According to the results of the study, awareness, and knowledge regarding the use of antibiotics were insufficient. Community pharmacists as specialist health professionals have a vital role in the rational use of antibiotics via patient education and monitoring. References: 1. Ling Oh A, Hassali MA, Al-Haddad MS, Syed Sulaiman SA, Shafie AA, Awaisu A. Public knowledge and attitudes towards antibiotic usage: a cross-sectional study among the general public in the state of Penang, Malaysia. J Infect Dev Ctries. 2011;5(5):338–347. Published 2011 May 28. doi:10. 3855/jidc.1502 2. Zaidi SF, Baroom MW, Ibrahim Hanbashi A, et al. Cross-Sectional Survey among General Population Regarding Knowledge and Attitude toward Antibiotic Usage in Western Saudi Arabia. Pharmacy (Basel). 2021;9(2):98. Published 2021 May 1. doi:10. 3390/pharmacy9020098 Disclosure of Interest: None Declared.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides